The Peculiarities of the Internal Position of Younger Schoolchildren with the Various Orientation of the Personality - A V Ivaschenko; L V Zubova; O A Scherbinina (Peoples' Friendship University of Russia (RUDN University), 2008)
The article submits some psychological features of the internal position of younger schoolchildren with various orientations of the personality. The basic directions of psychological support of the internal position of the personality of younger schoolchildren are proved in the article.